Unveiling the Synergy: Sciatica, Arthritis, and Their Integrated Approach to Wellness - Chandrika Kadam (International Journal of Vaccines, 2024)
This comprehensive review delves into the intricate connection between sciatica and arthritis, unraveling the etymological roots of “sciatica” from its ancient Greek and Latin origins. Tracing the historical aspects of sciatica back to the teachings of Hippocrates, the fifth-century BC Hellenic physician, sets the stage for a contemporary exploration of the interplay between these conditions. The sciatic nerve, including nerve roots spanning from L4 to S3, stands out as the largest nerve in the human body, boasting a diameter of up to 2 cm. This extensive nerve network is essential for motor function, offering direct support to a range of muscle groups in the lower extremities. Rheumatoid arthritis (RA), a chronic autoimmune disorder primarily affecting peripheral joints, typically spares spinal involvement but occasionally manifests with low back pain and sciatic radicular pain. Understanding the distinctive features of RA in the lumbosacral column enhances our grasp of its varied clinical presentations. In modern times, the review focuses on how sciatica and rheumatoid arthritis are related. RA primarily affects joints, but when it occasionally shows up in the lower back, it adds complexity to the clinical picture. The review explores the different ways RA-related sciatic nerve pain can present, highlighting the varied symptoms and potential challenges in diagnosing the condition. By looking at the historical roots and current aspects of sciatica and its link to rheumatoid arthritis, this review helps us better understand how these conditions interact. By combining ancient wisdom with modern medical insights, it offers a more complete perspective, aiming to improve the accuracy of diagnosis and enhance patient care in the complex world of sciatica and arthritis.
Keywords: Sciatica; arthritis; autoimmune disorder; lower back pain